Review Of Agroindustrial Strategic Studies, Researches And Development In Indonesia: The Case Of Oil Palm, Cacao And Gambir (Jurnal Teknologi Industri Pertanian, 2010)
Estate crops agroindustry has been playing very important role in the Indonesian economy, especially in contributing foreign exchanges and competitive image for the country. Recently, Indonesian Government, through the Ministry of National Education, has launched a national strategic research grant for three commodities, namely oil palm, cacao and gambir, due to their contributions as champions of the world. However, some problems are facing the global trade of the above mentioned commodities, so that some technological and managerial breakthroughs have to be found through research and development activities. This article reviews some progress in the development of oil palm, cacao and gambir agroindustries in Indonesia. Keywords: research and development, oil palm, cacao, gambir agroindustries.